Mixtures of tritiated water, zinc and dissolved organic carbon: Assessing interactive bioaccumulation and genotoxic effects in marine mussels, Mytilus galloprovincialis. (July 2018) - Pearson, Holly B.C.; Dallas, Lorna J.; Comber, Sean D.W.; Braungardt, Charlotte B.; Worsfold, Paul J.; Jha, Awadhesh N.
Abstract: Release of tritium ( 3 H) in the marine environment is of concern with respect to its potential bioaccumulation and detrimental impact on the biota. Previous studies have investigated the uptake and toxicity of this radionuclide in marine mussels, and the interaction of 3 H with dissolved organic ligands and elevated temperature. However, despite the well-established view that toxicity is partly governed by chemical speciation, and that toxic effects of mixture of contaminants are not always additive, there have been no studies linking the prevailing chemistry of exposure waters with observed biological effects and tissue specific accumulation of 3 H in combination with other constituents commonly found in natural waters. This study exposed the marine mussel Mytilus galloprovincialis for 14 days to mixtures of 3 H (as tritiated water, HTO) and zinc (Zn) at 5 Mbq L −1, and 383, 1913 and 3825 nM Zn, respectively, to investigate (a) 3 H and Zn partitioning in soft tissues of mussels, and (b) DNA damage in haemocytes, determined using the single cell gel electrophoresis or the comet assay. Additionally, the extent of association of 3 H with dissolved organic carbon (DOC, added as humic acid) over the exposure period was investigated in order to aid the interpretation of biological uptake and effects. Results concluded a clear antagonistic effect of Zn on 3 H-induced DNA damage at all Zn concentrations used, likely explained by the importance of Zn in DNA repair enzymes. The interaction of DOC with 3 H was variable, with strong 3 H-DOC associations observed in the first 3 d of the experiment. The secretion of 3 H-binding ligands by the mussels is suggested as a possible mechanism for early biological control of 3 H toxicity. The results suggest risk assessments for radionuclides in the environment require consideration of potential mixture effects. Highlights: Marine mussels exposed to tritiated water, zinc and organic carbon (humic acid), alone or in combinations for 14 days. Tritium and Zn partitioning in soft tissues in association with humic acid investigated. DNA damage in haemocytes and tissue-specific tritium accumulation varied with time. Interaction of humic acid variable; strong HTO-DOC association in the first 3 days. Antagonistic effect of Zn on HTO-induced DNA damage for the concentrations used.